PERAN GURU PENDIDIKAN AGAMA KATOLIK (PAK) DALAM MENINGKATKAN PERCAYA DIRI PESERTA DIDIK - Silitonga, Indah Teresia; Sembiring, Mimpin (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Self-confidence is the ability of individuals to believe in their own potential and not depend on others to develop positive attitudes and values in themselves. This study aims to identify the role of Catholic Religious Education teachers in increasing students' self-confidence at Santo Yoseph Private Junior High School Medan. The research method used is qualitative with a case study approach. Data were collected through observation, interview, and documentation. The results showed that Catholic Religious Education teachers have a significant role in increasing learners' self-confidence through a personal approach and interactive learning. Teachers help learners to be more opinionated and more confident in interacting in class. The findings provide an impression for the practice of education in schools, especially in developing learners' social skills and self-confidence. The results of this study also show that the confidence and self-confidence of learners at Santo Yoseph Private Junior High School Medan is still very low.